MANAJEMEN STRATEGI PENGELOLAAN SAMPAH DALAM MEWUJUDKAN ZERO WASTE DI KABUPATEN TAKALAR - Ariyanti, Nur Afrisa; Ansari, Muh Isa; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2023)
The main problem in this study is how to manage waste management strategies in realizing zero waste in Takalar district. This study uses qualitative research methods with descriptive research type. Data collection techniques used were observation, interviews and documentation. Research informants amounted to 5 people. Validation of data through triangulation of sources, techniques and time, then analyzed through data reduction, data presentation and drawing conclusions. The results of the study indicate that aspects of the formulation 1. Formulation in Strategic Management used is by educating and socializing related to waste transportation and pick-up services, some have been able to provide satisfaction to the community. In the second aspect, namely 2. Implementation is considered to be maximal enough even though there are still some that have not been implemented, where there needs to be adequate supervision and guidance so that the community can understand the impact that can be caused by waste. The third aspect of the evaluation shows that efforts to improve The problem of waste services carried out by the government already exists with the initiative in terms of the desire to further improve the quality of a good and clean environment.